Evaluation of antioxidant potential in fresh and boiled juice of purslane leaves - Balamurugan Pandiyan; Ranjithkumar Dhanaraj; Sumayya Rehaman; Sakthipraba Sampath; Malashree Lakshmanan; Anitha Jebamalai Raj; Sangilimuthu Alagar Yadav (International Journal of Research in Pharmaceutical Sciences, 2019)
Free radical scavenging potentials of fresh and cooked Purslane (Portulaca oleracea - Portulacaceae) was estimated by in vitro antioxidant assays. Antioxidant activity of fresh aqueous juice and cooked aqueous filtrate of purslane leaves were evaluated against synthetic free radicals such as DPPH, ABTS.+ and the results were comparable with that of the reference antioxidant L-Ascorbic acid. The juices showed high antioxidant activity using DPPH and ABTS.+ assays with increasing concentration of juice extracts. The total phenolic content was quantified and found to be 55.26±1.04 and 26.15 ±1.25 mg/g evaluated by the gallic acid corresponds to fresh and cooked filtrate respectively. The IC50 values of fresh, cooked filtrate and L- ascorbic acid were 145.15 ± 1.85, 85.35 ± 2.17 µg/ml and 65. 40 ± 3.66 µg/ml respectively in DPPH antioxidant assay and likewise the IC50 values of fresh, cooked filtrate and L-ascorbic acid found to be 227.35±1.45 µg/ml, 151.15±1.05 and 65.15±2.89 µg/ml, respectively in ABTS.+ antioxidant assay. Comparatively the inhibitory concentration of purslane leaves was high in cooked filtrate juice than the fresh aqueous juice.